PERANAN GURU DALAM MENGEMBANGKAN KEPERCAYAAN DIRI ANAK USIA 4-5 TAHUN DI TK MAZMUR 21 PONTIANAK SELATAN - Natalia, Silvi Efriska; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrackSelf-confidence is a personality trait that implies confidence in one's own abilities. Children Â self confidence is very influenced by how parents or educators grow their self confidence. A common issue in this study is "How Role of Teachers in Developing Self-Confidence in 4-5-Year-Old Children in Southern Pontianak Psalm 21". Of the general problems will be examined specific problems namely; how the teacher's role as a guide, motivator, and inspiration, in developing the confidence of children aged 4-5 years in Kindergarten Psalm 21. This research was conducted in the form of qualitative and descriptive research.The data collection tools are interview guidelines, observation guidelines, documentation data, and field note data. The results showed: (1) The role of the teacher as a guide in developing self-confidence by explaining to children in advance the tasks to be given. The teacher directs and helps the child if the child is having difficulties(2) The role of the teacher as a motivator in developing the child's confidence by encouraging, encouraging the child to have the courage to complete the task. 3) The role of the teacher as an inspiration in developing children's confidence by demonstrating or exemplifying the task at hand.Â Keywords: Teacher's role,Develop Children's Self Confidence